Pengaruh gaya kepemimpinan dan lingkungan kerja terhadap kinerja karyawan pada badan penanggulangan bencana daerah kabupaten bogor - Muhammad Tri Aji Saputro Saputro; M. Azis Firdaus (Indonesian Journal of Multidisciplinary on Social and Technology, 2024)
The purpose of this study is to analyze the influence of leadership style and work environment together on the performance of employees of the Bogor Regency Regional Disaster Management Agency. The type of research used in this study is a quantitative approach. In this study, the sample used was the total population in the Regional Disaster Management Agency of Bogor Regency, a research sample of 50 employees. The results of the study showed. There is a partial significant influence between Leadership Style on Employee Performance at the Bogor Regency Regional Disaster Management Agency the results show that the Influence of Leadership Style on Employee Performance has a significant effect, that the result of the Tcount value is 3.262 and the P value is 0.001. There is a partial significant influence between the Work Environment on Employee Performance at the Bogor Regency Regional Disaster Management Agency, the influence of Work Environment variables on Employee Performance with the value of the Original sample (O) path coefficient of 0.429 and significant with values = 0.001 < 0.05 Ha2. There is a significant influence simultaneously between Leadership and Work Environment on Employee Performance at the Bogor Regency Regional Disaster Management Agency. The contribution given by Leadership Style and Work Environment simultaneously to Employee Performance The influence of exogenous variables of Leadership Style through Work Environment on Employee Performance variables shows a very significant relationship where the T value is calculated 3.262 Original sample (O) = 0.364 and significant with values = 0.001 < 0.05 Ha4.